Laser Peening on Aluminum Alloy 7049 Using Black Paint Surface Coating - Alalkawi, H. J. M.; Sadkhan, Basim A.; Abed, Noor N. (Al-Khwarizmi Engineering Journal, 2015)
Abstract Black paint laser peening (bPLP) technique is currently applied for many engineering materials , especially for aluminum alloys due to high improvement in fatigue life and strength . Constant and variable bending fatigue tests have been performed at RT and stress ratio R= -1 . The results of the present work observed that the significance of the surface work hardening which generated high negative residual stresses in bPLP specimens .The fatigue life improvement factor (FLIF) for bPLP constant fatigue behavior was from 2.543 to 3.3 compared to untreated fatigue and the increase in fatigue strength at 107 cycle was 21% . The bPLP cumulative fatigue life behavior was improved by 1.786 at L-H and 1.55 at H-L due to black paint coating . Keywords: Constant and variable fatigue behavior , Black paint laser peening , 7049 Al- alloy .